Toward improved target conformity for two spot scanning proton therapy delivery systems using dynamic collimation - Moignier, Alexandra (Med Phys, 2016)
PURPOSE: To quantify improvement in target conformity in brain and head and neck tumor treatments resulting from the use of a dynamic collimation system (DCS) with two spot scanning proton therapy delivery systems (universal nozzle, UN, and dedicated nozzle, DN) with median spot sizes of 5.2 and 3.2 mm over a range of energies from 100 to 230 MeV. METHODS: Uncollimated and collimated plans were calculated with both UN and DN beam models implemented within our in-house treatment planning system for five brain and ten head and neck datasets in patients previously treated with spot scanning proton therapy. The prescription dose and beam angles from the clinical plans were used for both the UN and DN plans. The average reduction of the mean dose to the 10-mm ring surrounding the target between the uncollimated and collimated plans was calculated for the UN and the DN. Target conformity was analyzed using the mean dose to 1-mm thickness rings surrounding the target at increasing distances ranging from 1 to 10 mm. RESULTS: The average reductions of the 10-mm ring mean dose for the UN and DN plans were 13.7% (95% CI: 11.6%–15.7%; p < 0.0001) and 11.5% (95% CI: 9.5%–13.5%; p < 0.0001) across all brain cases and 7.1% (95% CI: 4.4%–9.8%; p < 0.001) and 6.3% (95% CI: 3.7%–9.0%; p < 0.001), respectively, across all head and neck cases. The collimated UN plans were either more conformal (all brain cases and 60% of the head and neck cases) than or equivalent (40% of the head and neck cases) to the uncollimated DN plans. The collimated DN plans offered the highest conformity. CONCLUSIONS: The DCS added either to the UN or DN improved the target conformity. The DCS may be of particular interest for sites with UN systems looking for a more economical solution than upgrading the nozzle to improve the target conformity of their spot scanning proton therapy system.